Hubungan Pengetahuan Dan Sikap Keluarga Dengan Pencegahan Penularan COVID-19 Di Wilayah Perumahan Ambar Waringin Jaya Bojong Gede Bogor Tahun 2021: The Relationship of Family Knowledge and Attitude with the Prevention of COVID-19 Transmission in the Ambar Waringin Jaya Housing Area Bojong Gede Bogor in 2021 - Evendi, Agus (Dohara POAJ, 2022)
Introduction: Knowledge and a good attitude are the keys to success in helping citizens to prevent the spread of COVID-19. Ignorance and indifferent attitude will cause COVID-19 to never end. The community has an important role in breaking the chain of spread and transmission of COVID-19. Methods: The type of research used in this research is descriptive-analytic research design with cross-sectional research. The method of determining the sample used in this study was done by simple random sampling with a total sample of 112 residents in the Ambar Waringin Jaya Housing Bojong Gede Bogor. Results: There is a significant relationship between knowledge and COVID-19 prevention with a correlation coefficient of 336,000 and p-value = 0.000. There is a significant relationship between family attitudes and COVID-19 prevention with a correlation coefficient of 3,924 and a p-value = 0.001. Discussion: Good family knowledge and attitudes toward preventing the transmission of COVID-19 are needed to break the chain of the spread of COVID-19.